Determinants of therapy switch in multiple sclerosis treatment-naïve patients: A real-life study. (August 2019) - Saccà, Francesco; Lanzillo, Roberta; Signori, Alessio; Maniscalco, Giorgia T; Signoriello, Elisabetta; Lo Fermo, Salvatore; Repice, Annamaria; Annovazzi, Pietro; Baroncini, Damiano; Clerico, Marinella; Binello, Eleonora; Cerqua, Raffaella; et al.
Background: With many options now available, first therapy choice is challenging in multiple sclerosis (MS) and depends mainly on neurologist and patient preferences. Objectives: To identify prognostic factors for early switch after first therapy choice. Methods: Newly diagnosed relapsing–remitting MS patients from 24 Italian centers were included. We evaluated the association of baseline demographics, clinical, and magnetic resonance imaging (MRI) data to the switch probability for lack of efficacy or intolerance/safety with a multivariate Cox analysis and estimated switch rates by competing risks models. Results: We enrolled 3025 patients. The overall switch frequency was 48% after 3 years. Switch risk for lack of efficacy was lower with fingolimod (hazard ratio (HR) = 0.50; p = 0.009), natalizumab (HR = 0.13; p < 0.001), dimethyl-fumarate (HR = 0.60; p = 0.037), teriflunomide (HR = 0.21; p = 0.031) as compared to interferons. Younger age (HR = 0.96; p < 0.001), diagnosis delay (HR = 1.23; p = 0.021), higher baseline Expanded Disability Status Scale (HR = 1.17; p = 0.001), and spinal cord lesions (HR = 1.46; p = 0.001) were independently associated with higher inefficacy switch rates. We found lower switch for intolerance/safety with glatiramer acetate (HR = 0.61; p = 0.001), fingolimod (HR = 0.35; p = 0.002), and dimethyl-fumarate (HR = 0.57; p = 0.022) as compared to interferons, while it increased with natalizumab (HR = 1.43; p = 0.022). Comorbidities were associated with intolerance switch (HR = 1.28; p = 0.047). Conclusion: Several factors are associated with higher switch risk in patients starting a first-line therapy and could be integrated in the decision-making process of first treatment choice.